THE CONTENTS OF THE EDUCATION IN THE NUNS BASILIAN’S DROGOBYCH TEACHER’S SEMINARY (1920 – 1936 - Haliv, Mykola (Mountain School of Ukrainian Carpaty, 2020)
The relevance of the study is due to the increasing attention of historians of pedagogy to the activities of the Church and monastic orders in the field of education. Among the Ukrainian monastic orders, which carried out an active educational work, the Order of St. Basilius Magnus (OSBM) was particularly distinguished, including his female branch – the nuns Basilian. It was the nuns Basilian who organized a women's teacher's seminary in Drohobych in the 1920-ies and 1930-ies. But nuns Basilian’s activities have not been sufficiently studied in historical and pedagogical science. The purpose of the article is to reveal the content of education in the Ukrainian private women's teacher's seminary of in the interwar Drohobych. The research is based on socio-cultural and lemological approaches, on the principles of historicism, systematicity, scientific. The author applied general scientific (analysis, synthesis, generalization) and special historical (historical-genetic, historical-typological, historical-systemic, documentary heuristics) methods. A foundations and main aspects of the activity of the OSBM’s teacher's seminary, the level of education of the seminary teachers, the number of students, the peculiarities of the educational process in the seminary are explored in this article. Therefore, during the interwar period, the OSBM’s nuns in Drohobych actively pursued two educational institutions within the walls of the monastery – a women's teacher's seminary and an elementary school. They were able to provide these facilities financially, to arrange for proper teaching staff, to gather a large number of students and pupils. An according to my calculations, the teacher's seminary of Basilian’s nuns trained more than 350 teachers, who later performed teaching duties in schools in the Drohobych region. The Basilian’s six-grade (and later seven-grade) primary school also provided a good elementary education for several hundred children from poor families and orphans. The prospect of further research is to study the activity of the Basilian’s women teacher's seminary in Yavoriv.